Gene Expression of Selected Apoptotic Markers in Human Oral Squamous Carcinoma HSC-3 Cell Line Treated with Myrmecodia Pendans Plant - Lestari, Widya; Zulhakim, Amir; Wan Yusry, Wan Nur Aisyah; Iskandar, Siti Hajar; Eddie, Mohd Syazwan Shah; Abd Aziz, Nurul Afiqah; Arief Ichwan, Solachuddin Jauhari; Irfan, Nining I.; Suriyah, Wastuti Hidayati (2021)
This poster was submitted to participate at the 11th Annual ISCC Conference and Congress organised by the Indonesian Society of Cancer and Chemopreventive, held on 9-21 November 2020.